1900 Ga. Laws 201 - (:unkn) unknown (My University, 1900)
§ 15: Granted the town council to regulate the keeping and selling of dynamite, gunpowder, kerosene, and all other hazardous articles of merchandise.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER